Respuesta :
Answer: The correct option is
(B) [tex]f^{-1}(x)=\dfrac{1}{x-1}.[/tex]
Step-by-step explanation: We are given to select the correct expression that is the inverse of the following function :
[tex]f(x)=\dfrac{x+1}{x}~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
Let y denotes f(x). Then,
[tex]y=f(x)~~~~~~\Rightarrow x=f^{-1}(y).[/tex]
Substituting this value in equation (i), we get
[tex]f(x)=\dfrac{x+1}{x}\\\\\\\Rightarrow y=\dfrac{f^{-1}(y)+1}{f^{-1}(y)}\\\\\\\Rightarrow yf^{-1}(y)=f^{-1}(y)+1\\\\\Rightarrow yf^{-1}(y)-f^{-1}(y)=1\\\\\Rightarrow (y-1)f^{-1}(y)=1\\\\\Rightarrow f^{-1}(y)=\dfrac{1}{y-1}\\\\\Rightarrow f^{-1}(x)=\dfrac{1}{x-1}.[/tex]
Thus, the required inverse of the given function is
[tex]f^{-1}(x)=\dfrac{1}{x-1}.[/tex]
Option (B) is CORRECT.